Molten salt synthesis of potassium-containing hydroxyapatite microparticles used as protein substrate - Weissmueller, N; Schiffter, H; Pollard, A; Tas, A (2014)
The bioactivity of a material may be favorably altered by exerting control over its protein sorption propensity. Spheroidal potassium-containing calcium phosphate bioceramic microparticles were manufactured by molten salt synthesis. The effects on particle characteristics and adsorption of bovine serum albumin (BSA) of different hydroxyapatite (HA, Ca10(PO4) 6(OH)2) to salt flux (K2SO4) ratios were investigated. X-ray diffraction (XRD) patterns showed the emergence of minor phases in addition to the HA major phase with increased salt flux. Synthesized particles were found to increase in potassium content with increasing HA:K2SO4 ratio. Conversely, the amount of BSA adsorption onto microparticles, normalized for surface area, decreased with excess K2SO4. The results indicate that K 2SO4 content can impact the morphology, composition, and BSA adsorption propensity of the resultant bioceramic microparticles. © 2014 Elsevier Inc. All rights reserved.